2020
DOI: 10.3390/jcm9030700
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial Lung Disease Associated with Lung Cancer: A Case–Control Study

Abstract: Interstitial lung disease (ILD) seems to be associated with an increased risk of lung cancer (LC) and to have a poorer prognosis than LC without ILD. The frequency of ILD in an LC cohort and its prognosis implication need to be better elucidated. This retrospective, observational, cohort study evaluated the frequency of ILD among LC patients (LC–ILD) diagnosed over a 2-year period. LC–ILD patients’ characteristics were compared to those with LC without ILD (LC–noILD). Lastly, we conducted a case–control study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…Previous studies about lung cancer and ILD (the majority of the studies have focused on patients with IPF and CPFE) have also demonstrated lower survival and higher mortality rate among patients with lung cancer and ILD as compared to patients with lung cancer only or IPF only or emphysema without lung cancer. Gibiot et al [ 6 ], found median survival of 9 months for patients with lung cancer and ILD as opposed to 18 months for those with lung cancer only. Tzouvelekis et al [ 12 ], recently reported a median survival of 14 months in patients with lung cancer and IPF from the time of lung cancer diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies about lung cancer and ILD (the majority of the studies have focused on patients with IPF and CPFE) have also demonstrated lower survival and higher mortality rate among patients with lung cancer and ILD as compared to patients with lung cancer only or IPF only or emphysema without lung cancer. Gibiot et al [ 6 ], found median survival of 9 months for patients with lung cancer and ILD as opposed to 18 months for those with lung cancer only. Tzouvelekis et al [ 12 ], recently reported a median survival of 14 months in patients with lung cancer and IPF from the time of lung cancer diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In two separate meta-analyses SCC was also found to be the most common histology with 38% and 42% followed by adenocarcinoma with 31% and 34%, respectively [ 5 , 7 ]. A few studies have shown that, adenocarcinoma is the most common histologic type with SCC being second to adenocarcinoma [ 6 , 25 ]. Gibiot et al recently found adenocarcinoma to be the most common histologic type in 49 patients with lung cancer and concurrent ILD (47%) followed by SCC (20%) [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well established that inflammatory processes are associated with risk of lung cancer [6][7][8][9], and it is plausible that an individual's systemic inflammatory profile prior to a lung cancer diagnosis may be associated with mortality. In support of this hypothesis, inflammatory conditions such as chronic bronchitis and emphysema, chronic obstructive pulmonary disease (COPD), interstitial lung disease, and diabetes are associated with increased lung cancer mortality independent of their associations with increased lung cancer risk [10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…It is well-established that in ammatory processes are associated with risk of lung cancer [6][7][8][9], and it is plausible that an individual's systemic in ammatory pro le prior to a lung cancer diagnosis may be associated with mortality. In support of this hypothesis, in ammatory conditions such as chronic bronchitis and emphysema, chronic obstructive pulmonary disease (COPD), interstitial lung disease, and diabetes are associated with increased lung cancer mortality independent of their associations with increased lung cancer risk [10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%